1985
DOI: 10.1136/bmj.291.6505.1305
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of methylprednisolone pulses and low dose oral prednisone for the minimal change nephrotic syndrome.

Abstract: In a multicentre, randomised, prospective trial 89 patients (67 children and 22 adults) with the minimal change nephrotic syndrome were treated with three intravenous pulses of methylprednisolone followed by low dose oral prednisone for six months (group given methylprednisolone) or with high dose oral prednisone for four weeks followed by low dose oral prednisone for five months (control group). Five patients in the group given methylprednisolone and one in the control group did not respond initially. The tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…A small Italian randomized controlled trial of 67 pediatric and 22 adult MCD patients reported no efficacy of mPSL in accelerating remission and reducing relapse in 22 adult MCD patients (19). A Japanese retrospective cohort study reported a significantly higher incidence rate of relapse in patients treated with mPSL followed by PSL than in those patients who received PSL only (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small Italian randomized controlled trial of 67 pediatric and 22 adult MCD patients reported no efficacy of mPSL in accelerating remission and reducing relapse in 22 adult MCD patients (19). A Japanese retrospective cohort study reported a significantly higher incidence rate of relapse in patients treated with mPSL followed by PSL than in those patients who received PSL only (13).…”
Section: Discussionmentioning
confidence: 99%
“…An Italian randomized controlled trial showed that pediatric (not adult) MCD patients treated with mPSL and prednisone achieved remission earlier than those patients with prednisone alone (19). In another Japanese nonrandomized controlled trial of adult MCD patients, initial mPSL use followed by cyclosporine (not a Departments of *Geriatric Medicine and Nephrology, and corticosteroid) resulted in shorter time to remission compared with cyclosporine monotherapy and prednisolone (PSL) monotherapy (20).…”
Section: Introductionmentioning
confidence: 99%
“…Imbasciati et al 34 performed a multicenter, randomized, prospective trial in 89 patients with MCD, 22 of whom were adults. The study group received intravenous methylprednisolone for 3 days (20 mg/kg per day) followed by low-dose prednisone for 6 months (starting dose of 0.5 mg/kg per day in adults for 4 weeks followed by taper over 5 months).…”
Section: Efficacymentioning
confidence: 99%
“…5). Furthermore, although Imbasciati et al (13) did not describe adult patients who had cosmetic problems in detail, there were fewer patients in the enhanced treatment group who developed obesity, facies, striae or other cosmetic problems.…”
Section: Adverse Events Of Treatmentmentioning
confidence: 98%
“…Six of the seven studies, involving 308 patients, published the effect of enhanced steroid therapy on the relapse rate in adult patients with MCNS (9)(10)(11)(12)(13)15). Patients were assigned to the enhanced treatment group (n=144) and the control group (n=164).…”
Section: Effect On Relapse Ratementioning
confidence: 99%